The glorious World Cup : a fanatic's guide - Black, Alan.; Sterry, David (New York, N.Y. : New American Library, 2010)
This guide to soccer's ultimate tournament includes trivia, tall tales, statistics, quizzes and photographs, as well as profiles of famous players, villains, heroes and hooligans and commentary from famous fans.
Keywords: Soccer -- Tournaments -- South Africa; Soccer teams; Soccer players